2009
DOI: 10.1002/mnfr.200700379
|View full text |Cite
|
Sign up to set email alerts
|

Alternariol acts as a topoisomerase poison, preferentially affecting the IIα isoform

Abstract: Alternariol (AOH), a mycotoxin formed by Alternaria alternata, has been reported to possess genotoxic properties. However, the underlying mechanism of action is unclear. Here, we tested the hypothesis that interactions with DNA-topoisomerases play a role in the DNA-damaging properties of AOH. First we compared DNA-damaging properties of AOH with other Alternaria mycotoxins such as AOH monomethyl ether (AME), altenuene and isoaltenuene. AOH and AME significantly increased the rate of DNA strand breaks in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
164
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(179 citation statements)
references
References 31 publications
7
164
0
8
Order By: Relevance
“…AOH has been recently characterised as an inhibitor of DNA topoisomerase I and II with a certain selectivity for the II alpha isoform (Fehr et al, 2009). DNA topoisomerases are enzymes responsible for regulation of genomic DNA supercoiling and participate in essential processes of cells such as replication, transcription, recombination, repair, etc.…”
Section: Mechanism Of Genotoxicitymentioning
confidence: 99%
“…AOH has been recently characterised as an inhibitor of DNA topoisomerase I and II with a certain selectivity for the II alpha isoform (Fehr et al, 2009). DNA topoisomerases are enzymes responsible for regulation of genomic DNA supercoiling and participate in essential processes of cells such as replication, transcription, recombination, repair, etc.…”
Section: Mechanism Of Genotoxicitymentioning
confidence: 99%
“…Recent studies have shown that AOH and AME are able to induce DNA strand breaks, micronuclei and gene mutations in various cultured mammalian cells [5][6][7], and to inhibit topoisomerase I and IIa under cell-free conditions [8]. Moreover, AOH and AME are prone to cytochrome P450 (CYP)-mediated hydroxylation in vitro, leading to catechol and hydroquinone metabolites [9].…”
Section: Introductionmentioning
confidence: 99%
“…They have been reported to exhibit cytotoxic, fetotoxic, teratogenic, and possible mutagenic and estrogenic effects (24)(25)(26)(27) and may contribute to development of human esophageal cancer (28). AOH has been demonstrated to inhibit cholinesterase (29) and topoisomerases I and II (30). Furthermore, it was shown that AOH induces DNA damage and cell cycle arrest in vitro in the murine macrophage RAW 264.7 cell line, and the treated cells exhibited an abnormal nuclear morphology (31,32).…”
mentioning
confidence: 99%